Environmental impact assessment of raw material input and production process on Malaysian wood-based panel products / Syahirah Jusoh - Jusoh, Syahirah (2015)
In this study, an environmental impact assessment was conducted on three wood-based panel products namely particleboard, MDF and plywood. The objectives of this study were to determine and assess the environmental impacts of wood-based panel products and to compare the environmental impacts between these panel products and between three different subsystem which are panel preparation, panel shaping and panel finishing, th e scope of this study covers the whole process of particleboard, MDF and plywood manufacturing from the raw material preparation until board finishing (gate-to-gate LCA). Input and output data were collected through survey questionnaire that was developed for easy understanding and distributed to industries. The results from SimaPro 7.2 Software showed that the among three products i.e particleboard, MDF and plywood, the environmental impact on each of the ten categories is greatest for the particleboard followed by plywood and MDF. This could be explained by logs, resin and energy consumption in the particleboard production was higher compared to MDF and plywood. However, one-way analysis of variance (ANOVA) showed no significant difference between the three different products in terms of their effects on environmental impacts. For the most part, the highest impact categories for three wood-based panel products were being respiratory inorganic, climate change and fossil fuel. Meanwhile, the results for different production subsystems indicated that board shaping subsystem was the highest contributor for all wood-based panel products. As a conclusion, the findings from this study could provide an awareness about the Malaysian wood-based panel products industry particularly particleboard, MDF and plywood in terms of the contribution to environmental impact.